#### Answer

$\dfrac{16+15i}{-3i}=-5+\dfrac{16}{3}i$

#### Work Step by Step

$\dfrac{16+15i}{-3i}$
Multiply the numerator and the denominator of this expression by the complex conjugate of the denominator:
$\dfrac{16+15i}{-3i}=\dfrac{16+15i}{-3i}\cdot\dfrac{3i}{3i}=\dfrac{3i(16+15i)}{-9i^{2}}=\dfrac{3(16i+15i^{2})}{-9i^{2}}=...$
Substitute $i^{2}$ with $-1$ and simplify:
$...=\dfrac{3[16i+15(-1)]}{-9(-1)}=\dfrac{3(16i-15)}{9}=\dfrac{-15+16i}{3}=...$
$...=-\dfrac{15}{3}+\dfrac{16}{3}i=-5+\dfrac{16}{3}i$